Diagnóstico situacional e análise espacial da logística reversa de medicamentos domiciliares vencidos ou em desuso em uma rede varejista do Brasil - OLIVEIRA, Camila Martins (Universidade Federal do Pará, 2023)
Introduction: The reverse logistics process of disused or expired medicine for the general population makes the reverse flow, returning along its production and distribution chain, to have its final disposal environmentally sound. In this sense, the pharmacist is fundamental because he plays the role of knowledge multiplier, qualifying, training, and instructing employees and consumers about good environmental practices related to health waste. Objective: To carry out a situational diagnosis of reverse logistics and spatial analysis of expired or disused household medications in a pharmaceutical retail chain in Brazil. Method: It is an exploratory, cross sectional, and prospective study that used product/waste information obtained at different collection points in a network of pharmacies with 400 establishments in Brazil, from 2020 to 2022. Results: The study showed that the network collected a volume of 4,519.74 kg of expired medicines from the population between 2020 and 2022, concentrating the largest collection volume in the North region (69.1%). It is also noteworthy that Belem was the municipality with the highest collection, concentrating 92.5% of the collection in the state of Pará. Another important point was the presentation of a manual for the implementation of reverse logistics for expired medicines for the population. Conclusion: The findings of this study should contribute to the improvement and application of reverse logistics for expired medicines for the population in Brazil.